Modelling of antibiotic resistance in aquatic systems: a useful tool to protect human and ecosystem health - Jampani, Mahesh; Mateo-Sagasta, Javier (International Water Management Institute, 2023)
Antibiotic resistance in aquatic systems puts the health of people and animals at risk from diseases caused by antibiotic-resistant bacteria. Scientists at the International Water Management Institute (IWMI) are working with research partners on modelling of water quality to understand how antibiotic-resistant bacteria and antibiotic resistance genes are transmitted in water systems. Their findings will guide interventions aimed at reducing water pollution and the spread of antibiotic resistance. In this post, IWMI researchers Mahesh Jampani and Javier Mateo-Sagasta discuss how water quality modelling can help tackle the threat of antibiotic resistance.